Burn out Syndrome Geriatric Health Team “For Dignified and Quality Care Medicine for the Well-Being of the Health Team of People Who Suffer” - Diaz Gerevini, G. T. (2025)
The influence of Covid-19 on mental health of employees and its impact on the work culture in the textile sector has been investigated. The objective has been to study the influences of Covid-19 on mental Health of workers and to assess the impact of mental health on organizational Work Culture. Available literature has been reviewed. It was concluded that there is a significant impact of Covid-19 on the mental health of employees. Employees faced mild to severe symptoms of depression, anxiety and distress due to prolonged working hours, change in work dynamics, isolation etc. The impact of mental health of employees also affected the work culture in organizations to some extent. A shift in work culture dynamics has been observed due to work from home and virtual mode of communication during Covid-19 pandemic. The investigation sheds light on how Covid-19 has affected employees working in different industries and locations and how the impact of their mental health has changed the work culture of organization.